Pain - Moscoso, J. author. aut Link
XIII, 301 p.
Keywords: Halfway between history and philosophy, this book deals with the historical forms that have permitted the understanding of human suffering from the Renaissance to the present. Representation, sympathy, imitation, coherence and narrativity are but a few of the rhetorical recourses that men and women have employed in order to feel our pain.